Add-on deep transcranial magnetic stimulation (dTMS) in patients with dysthymic disorder comorbid with alcohol use disorder: A comparison with standard treatment. (January 2015) - Girardi, Paolo; Rapinesi, Chiara; Chiarotti, Flavia; Kotzalidis, Georgios D.; Piacentino, Daria; Serata, Daniele; Del Casale, Antonio; Scatena, Paola; Mascioli, Flavia; Raccah, Ruggero N.; Brugnoli, Roberto; Digiacomantonio, Vittorio; et al.
Abstract: Objectives. Dorsolateral prefrontal cortex (DLPFC) is dysfunctional in mood and substance use disorders. We predicted higher efficacy for add-on bilateral prefrontal high-frequency deep transcranial magnetic stimulation (dTMS), compared with standard drug treatment (SDT) in patients with dysthymic disorder (DD)/alcohol use disorder (AUD) comorbidity. Methods. We carried-out a 6-month open-label study involving 20 abstinent patients with DSM-IV-TR AUD comorbid with previously developed DD. Ten patients received SDT for AUD with add-on bilateral dTMS (dTMS-AO) over the DLPFC, while another 10 received SDT alone. We rated alcohol craving with the Obsessive Compulsive Drinking Scale (OCDS), depression with the Hamilton Depression Rating Scale (HDRS), clinical status with the Clinical Global Impressions scale (CGI), and global functioning with the Global Assessment of Functioning (GAF). Results. At the end of the 20-session dTMS period (or an equivalent period in the SDT group), craving scores and depressive symptoms in the dTMS-AO group dropped signiﬁcantly more than in the SDT group ( P < 0.001 and P < 0.02, respectively). Conclusions. High frequency bilateral DLPFC dTMS with left preference was well tolerated and found to be effective as add-on in AUD. The potential of dTMS for reducing craving in substance use disorder patients deserves to be further investigated.